2002
DOI: 10.2307/4003998
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Grazing on Channel Morphology of Intermittent Streams

Abstract: Alteration of stream channel morphology by cattle and associated streambank erosion is a concern on rangeland watersheds. The objective of this study was to determine changes in stream channel morphology in response to 5 grazing treatments applied to 0.4 ha pastures and replicated on 3 intermittent streams at the San Joaquin Experimental Range in the central Sierra Nevada foothills of California. Baseline stream channel morphology parameters were determined along 10 transects in each pasture in June 1994. Seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Although lush vegetation within the exclosure suggested narrowing of the channel, channel width was not significantly different from grazed reaches outside the exclosure. Similarly, Allen-Diaz et al (1998) and George et al (2002) did not detect any morphological changes to headwater streams located in seasonally grazed pastures in the Sierra Foothills of California. Platts and Nelson (1985) evaluated stream response to the removal of livestock pressures along Big Creek in northeastern Utah.…”
Section: Exclusion Fencing/riparian Buffersmentioning
confidence: 80%
“…Although lush vegetation within the exclosure suggested narrowing of the channel, channel width was not significantly different from grazed reaches outside the exclosure. Similarly, Allen-Diaz et al (1998) and George et al (2002) did not detect any morphological changes to headwater streams located in seasonally grazed pastures in the Sierra Foothills of California. Platts and Nelson (1985) evaluated stream response to the removal of livestock pressures along Big Creek in northeastern Utah.…”
Section: Exclusion Fencing/riparian Buffersmentioning
confidence: 80%
“…However, trend analysis of the monthly erosion/ deposition data from 2005 through 2007 showed that RS pastures had an increasing trend (i.e., a decrease in bank erosion), whereas no trend was observed in CSU and CSR pastures (Nellesen et al, 2011). Although studies have shown signifi cant reductions in stream bank erosion resulting from cattle exclusion (Kauff man et al, 1983;Trimble, 1994;Zaimes et al, 2008), other studies have not (Allen-Diaz et al, 1998;George et al, 2002;Nellesen et al, 2011). Th ese results suggest that the eff ect of cattle on stream bank erosion is site-or method specifi c. In the current study, stream bank erosion was variable within treatments and seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other studies have suggested that geology mediates the relationship between ungulate influences and trout populations. For example, sandy and gravelly riparian soils are often less vulnerable to ungulate-induced bank erosion than are finer-textured soils (Nelson et al 1992;George et al 2002). Furthermore, Knapp et al (1998) reported that grazing increased numbers of golden trout in a felsic (granitic) meadow system by creating more suitable spawning habitat.…”
Section: Evaluating Influences Of Ungulate Grazing On Trout Habitatmentioning
confidence: 99%
“…Moreover, studies to determine the impacts of grazing on fishes have often been compromised by weak experimental designs (Platts 1991;Rinne 1999). Large experimental errors commonly result from high variation across and within streams, causing an inability to detect statistically significant differences (Larsen et al 1998;George et al 2002). Attempts to evaluate impacts of agricultural land use on fisheries have often been complicated by complex interrelationships with geologic variation at different scales (Fitzpatrick et al 2001).…”
Section: Introductionmentioning
confidence: 99%